Effect of capillarity on fourth order nonlinear evolution equation for two stokes wave trains in deep water in the presence of air flowing over water - Dhar, Asoke Kumar; Mondal, J. (Zielona Góra: Uniwersytet Zielonogórski)
Fourth order nonlinear evolution equations, which are a good starting point for the study of nonlinear water waves, are derived for deep water surface capillary gravity waves in the presence of second waves in which air is blowing over water. Here it is assumed that the space variation of the amplitude takes place only in a direction along which the group velocity projection of the two waves overlap.
Keywords: nonlinear evolution equation; surface capillary gravity wave; stability